Fighter pilot : the first American ace of World War II - Dunn, William R., 1916- (University Press of Kentucky, 1982)
In 1939, a young American named William R. Dunn crossed the Canadian border with the intention of voluntering for the Royal Canadian Air Force. Winding up in the infantry instead, he was later transferred to the RCAF and was the first pilot in the famous Eagle Squadron of American volunteers to shoot down an enemy aircraft. He later became the first American ace of the war.